Gender Inequality in Scientometric Research: A Case Study of Scientometrics Journal - Gundur, Beeresh N; B T, Sampath Kumar (Journal of Data Science, Informetrics, and Citation Studies)
This study examines gender inequalities in research productivity and citation impact among first authors in Scientometrics journal from 2020 to 2024. It examines the representation of male and female first authors, their research output, and citation patterns, shedding light on persistent gender gaps in scientometric research. A bibliometric analysis was conducted using data from the Scopus database, encompassing 1734 articles and review papers published in Scientometrics journal. The gender of first authors was identified using the Namsor platform. Research productivity, citation counts, and single-authored contributions were analyzed to assess gender-based trends. Male authors dominated research productivity as first authors (64.01%) compared to female authors (35.99%). Similarly, 71% of single authored publications were observed by male researchers. Analysis of citations also shown the discrepancies like male first authors acknowledged 69% of total citations while 31% of share by female first authors. Apart from that, 75% of citations were noticed by male single authors compare to female single authors with 25% only. These trends reveal the underrepresentation of female participation in research productivity and citation impact. The study assesses the contribution and active involvement of female authorship in research productivity and impact compare to male counterpart considering the reputed journal indexed in Scopus with Citescore 7.2. The observations and findings would be valuable and perceptive for the researchers involved in scientometric studies.
Keywords: Gender Disparity; Research Productivity; Scientometrics; Citations; Bibliometrics; Global South; Global North.